Situational analysis of Nyamagana Social-Ecological Landscape in the Cibitoke Province of Burundi - Niyuhire, M. C.; Emera, W. D.; Kagisye, A.; Havyarimana, D.; Niyoyankunze, J. M. V.; Nkurunziza, C.; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
In the developing world, the drivers behind changes in social ecological landscapes (SEL) are intricate and have been steadily intensifying over the years. Regions blessed with abundant natural resources, encompassing fertile soils, lush forests, freshwater bodies, valuable minerals, and more, tend to experience rapid population growth and heightened poverty rates. This often results in a heightened demand for essential livelihood components, including access to alternative livelihoods, education, food, healthcare, water, forest resources, housing, roads, and spaces for agriculture and aquaculture. Furthermore, the intersection of multiple national and global stakeholders continues to exert substantial pressure on exploiting natural resources at the sub-national level. To address the pervasive issue of land degradation, particularly in developing nations like Burundi, the implementation of landscape surveying and mapping emerges as a crucial tool. These methods provide valuable insights into ecosystem services and their interactions, paving the way for sustainable landscape conservation. Employing the Driver-Pressure-State-Impact-Response (DPSIR) for Social-Ecological Landscape (SEL) assessment framework, a diverse array of methodologies was employed in the current study, with a focus on the sub-Nyamagana watershed on the Imbo plain in Burundi. This research aims to conduct a comprehensive situational analysis, shedding light on how drivers and pressures converge to define the state and impacts of SEL, while also emphasizing institutional and stakeholder responses. To delve deeper into the intricacies of the Nyamagana watershed, a complementary approach involving focus group discussions and individual questionnaires was undertaken. The survey covered a total of 166 households and six focus group discussions, each comprising twelve participants. The findings highlighted several factors and pressures, predominantly stemming from the intensive utilization of natural resources, as well as biotic and abiotic constraints such as drought, flooding, pests, diseases, and anthropogenic pressures like anarchic mining and rapid population growth. Of notable concern is the complexity of soil use and land cover, especially the widespread use of chemicals such as synthetic fertilizers and pesticides, which pose significant threats to ecosystem components. The social-ecological dynamics are characterized by a combination of ecological factors, including environmental disturbances like heavy rains, prolonged dry seasons, fires, deforestation, and climate change. The social component of the system encompasses all human activities, spanning the economy, technology, politics, and culture, that result in intricate interactions between communities and ecosystems. Within the Nyamagana watershed, various institutions play a crucial role in landscape management, with identified stakeholders including research services (e.g., ISABU, IRRI, IITA, and Burundi University), extension services (e.g., BPEAE, NGOs, and projects), and policy entities (such as the local administration and mixed committees for water management). The study underscores the looming threats to biodiversity, livelihoods, and ecosystem processes, particularly in the provision of soil and irrigation water, due to soil erosion by landslide, unsustainable mining activities and the unsustainable utilization of natural resources. Addressing these challenges necessitates a comprehensive and collaborative approach involving both local and global stakeholders to foster sustainable development and conservation efforts.